Entre Costas da África e a praça mercantil do Rio de Janeiro: os conflitos entre comércio e saúde na sociedade luso-brasileira oitocentista. - Wederson de Souza Gomes (Temporalidades, 2020)
This article intends to analyze the conflicts between the physicist-chief, Manoel Vieira da Silva and the Commerce Body of Rio de Janeiro. Regulated by the royal charter in 1808, the duties of chief surgeon and chief physicist were linked to the practice of medicine, inspection of apothecaries, customs and drug stores both in the colonial portion and on the peninsula. These health agents were also in control of the arrival of vessels with African slaves in the ports of Rio de Janeiro. From the year 1808 onwards, a series of conflicts began between the Physicist-Major and the businessmen of the market square in Rio de Janeiro. This is because part of the control measures directly interfered in the taxation and trade of the enslaved, the main Rio de Janeiro wholesalers acted in a way to modify legislation that reverberated about their businesses, which led to a clash with the chief provider. Thus, we will seek to expose the link between the mercantile tract and health activities because we understand that they explain aspects about the colonial mercantile economy and the other royal institutions.